Partisipasi anggota pokdarwis dalam program desa binaan untuk pengembangan ekowisata terintegrasi di Kampung Rawa Mekar Jaya Kecamatan Sungai Apit Kabupaten Siak - Nurul Qomar; Ahmad Muhammad; Idwar Idwar; Sigit Sutikno; Zuli Laili Isnaini; Ahmad Nawawi; Romie Jhonnerie (Unri Conference Series: Community Engagement, 2019)
In 2016, a number of villagers in Kampung Rawa Mekar Jaya founded a ”pokdarwis,” a group of villagers who were eager to manage a remnant of mangrove forest for ecotourism, which is situated on the bank of Rawa River. The establishment of touristic infrastructure and the continuing promotion have attracted visitors from other localities. However, the increasing number of visitors has caused damages of the existing infrastructure. During 2018-2019, Riau University’s Institute for Researches and Community Services has launched a Village Foster Program in Kampung Rawa Mekar Jaya with the objective of improving local community’s capability of managing the mangrove forest remnant, particularly by integrating ecotourism with stingless beekeeping for honey production. Some activities that have been done included: (a) mapping of mangrove forest; (b) mangrove tree naming and labelling; (c) training for mangrove eco-guiding; (d) establishment of stingless beekeeping site with enriched food plants. Members of pokdarwis showed enthusiasm by joining these activities since they were aware of the importance of these activities. However, it was the leader of the pokdarwis who has played a more important role as a motivator with remarkable attitudes, such as being honest, dependable and highly praising equality.